CHAT SA: Modification of a Public Engagement Tool for Priority Setting for a South African Rural Context - Aviva Tugendhaft; Marion Danis; Nicola Christofides; Kathleen Kahn; Agnes Erzse; Marthe Gold; Rhian Twine; Audrey Khosa; Karen Hofman (Kerman University of Medical Sciences, 2022)
BackgroundGlobally, as countries move towards universal health coverage (UHC), public participation in decision-making is particularly valuable to inform difficult decisions about priority setting and resource allocation. In South Africa (SA), which is moving towards UHC, public participation in decision-making is entrenched in policy documents yet practical applications are lacking. Engagement methods that are deliberative could be useful in ensuring the public participates in the priority setting process that is evidence-based, ethical, legitimate, sustainable and inclusive. Methods modified for the country context may be more relevant and effective. To prepare for such a deliberative process in SA, we aimed to modify a specific deliberative engagement tool - the CHAT (Choosing All Together) tool for use in a rural setting. MethodsDesktop review of published literature and policy documents, as well as 3 focus groups and modified Delphi method were conducted to identify health topics/issues and related interventions appropriate for a rural setting in SA. Our approach involved a high degree of community and policy-maker/expert participation. Qualitative data were analysed thematically. Cost information was drawn from various national sources and an existing actuarial model used in previous CHAT exercises was employed to create the board. ResultsBased on the outcomes, 7 health topics/issues and related interventions specific for a rural context were identified and costed for inclusion. These include maternal, new-born and reproductive health; child health; woman and child abuse; HIV/AIDS and tuberculosis (TB); lifestyle diseases; access; and malaria. There were variations in priorities between the 3 stakeholder groups, with community-based groups emphasizing issues of access. Violence against women and children and malaria were considered important in the rural context. ConclusionThe CHAT SA board reflects health topics/issues specific for a rural setting in SA and demonstrates some of the context-specific coverage decisions that will need to be made. Methodologies that include participatory principles are useful for the modification of engagement tools like CHAT and can be applied in different country contexts in order to ensure these tools are relevant and acceptable. This could in turn impact the success of the implementation, ultimately ensuring more effective priority setting approaches.